2015
DOI: 10.1038/srep15795
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Sequence Features Regulate the Formation of the FG Network at the Center of the Nuclear Pore Complex

Abstract: The nuclear pore complex (NPC) is the portal for bidirectional transportation of cargos between the nucleus and the cytoplasm. While most of the structural elements of the NPC, i.e. nucleoporins (Nups), are well characterized, the exact transport mechanism is still under much debate. Many of the functional Nups are rich in phenylalanine-glycine (FG) repeats and are believed to play the key role in nucleocytoplasmic transport. We present a bioinformatics study conducted on more than a thousand FG Nups across 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 51 publications
(116 reference statements)
0
39
0
Order By: Relevance
“…Due to the eight-fold symmetry of the NPC5859, the cytoplasmic periphery, central channel, and nuclear basket each contain 24, 80, and 32 agents, respectively, representing the distribution of FG Nups60. In addition to these FG agents, non-FG agents are added to the channel to represent regions of the Nups that lack affinity for transport receptors but play a role in sterically repelling molecules, with the sum of the volume of these Nups corresponding to experimentally reported volumes60 (please refer to616263 for recent comprehensive reviews on NPC and6465666768 for detailed analysis of the behaviour of FG Nups). The collection of agents representing the mRNA is free to diffuse throughout the system while FG agents and non-FG agents are restricted to movement within their respective pore regions in order to maintain the permeability barrier.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the eight-fold symmetry of the NPC5859, the cytoplasmic periphery, central channel, and nuclear basket each contain 24, 80, and 32 agents, respectively, representing the distribution of FG Nups60. In addition to these FG agents, non-FG agents are added to the channel to represent regions of the Nups that lack affinity for transport receptors but play a role in sterically repelling molecules, with the sum of the volume of these Nups corresponding to experimentally reported volumes60 (please refer to616263 for recent comprehensive reviews on NPC and6465666768 for detailed analysis of the behaviour of FG Nups). The collection of agents representing the mRNA is free to diffuse throughout the system while FG agents and non-FG agents are restricted to movement within their respective pore regions in order to maintain the permeability barrier.…”
Section: Methodsmentioning
confidence: 99%
“…Although nucleocytoplasmic transport has been the focus of many computational and experimental studies in the past few decades [ 11 , 19 , 24 , 27 33 ], the role of sequence composition of FG Nups has only recently drawn attention amongst researchers of the field [ 24 26 , 28 , 29 , 34 ]. It has been observed that compositional changes in the sequences of FG Nups significantly influence the distribution of FG Nups inside the pore [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 These Nups are rich in phenylalanineglycine repeats, therefore called FG Nups, and are suggested to play the chief role in active transport of cargos through the NPC via formation of weak interactions with transporters. While various computational and experimental studies have explored the transport through the NPC, 1,3,27,48,51,54,66,72,73,76,87,99 the underlying mechanism of this process remains elusive.…”
Section: Introductionmentioning
confidence: 99%